One-step synthesis of petals-like graphitic carbon nitride nanosheets with triazole defects for highly improved photocatalytic hydrogen production. (28th January 2019) - Wen, Xue; Sun, Na; Tan, Yigen; Wang, Wenbin; Yan, Chunjie; Wang, Hongquan
Abstract: Reaction atmospheres during graphitic carbon nitride preparation can have a significant influence on the chemical composition and structure of the material, subsequently improving the photocatalytic activity. However, it is still a challenge to introduce an atmosphere by one-step heat-treated method to synthesis graphitic carbon nitride without additive gases. Herein, we developed a new one-step method to gather a variety of gases for preparing petals-like graphitic carbon nitride nanosheets (CNC), such as CO(g), NH3 (g) and H2 O(g). NH3 (g) and H2 O(g) are respectively derived from melamine-cyanuric acid supermolecule during pyrolysis. The petals-like CNC with more triazole defects (Nc) significantly increases the separation efficiency and the mobility of photogenerated photo-induced electron-hole pairs. Compared with the g-C3 N4 calcined under nitrogen atmosphere (CNN), CNC has smaller grain, higher porosity with larger surface area, and remarkably longer lifetime of charge carriers. As expected, the product CNC exhibited a hydrogen evolution rate of 1334 μmol g −1  h −1 under visible-light irradiation, which was 2.8 times higher activity than CNN, as well as higher than most of the reported bulk g-C3 N4 . Graphical abstract: Highlights: Multiple favorable gases were combined to synthesis g-C3 N4 by one-step calcination. The average H2 evolution rate of CNC was 2.8 times higher than CNN. Better visible-light photocatalytic performance was due to triazole defects.